Faktor Penentu Pemahaman Mahasiswa Akuntansi Era Covid19 (Studi Empiris Mahasiswa Akuntansi di Jawa Timur) - Tita Nawangsari, Ajeng (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2020)
This study aims to provide empirical evidence regarding the factors that affect student’s understanding in accounting during Covid 19 pandemic in East Java. There are there variables tested which are learning from home that represent the attitude and behavior of accounting students, the avalilability of IT and students understanding regarding the accounting knowledge. This study is a quantitative method to empirically tested those factors. Sampling method was carried out using a proportional random sampling technique and data was collected using a survey method through an online questionnaire. The results showed that the learning from home variable and the availability of IT had a significant positive effect on students' accounting understanding.